Complementary methods for SARS-CoV-2 diagnosis in times of material shortage - Thaisa Lucas Sandri (Nature Portfolio, 2021)
Abstract The pandemic caused by SARS-CoV-2 resulted in increasing demands for diagnostic tests, leading to a shortage of recommended testing materials and reagents. This study reports on the performance of self-sampled alternative swabbing material (ordinary Q-tips tested against flocked swab and rayon swab), of reagents for classical RNA extraction (phenol/guanidine-based protocol against a commercial kit), and of intercalating dye-based one-step quantitative reverse transcription real-time PCRs (RT-qPCR) compared against the gold standard hydrolysis probe-based assays for SARS-CoV-2 detection. The study found sampling with Q-tips, RNA extraction with classical protocol and intercalating dye-based RT-qPCR as a reliable and comparably sensitive strategy for detection of SARS-CoV-2—particularly valuable in the current period with a resurgent and dramatic increase in SARS-CoV-2 infections and growing shortage of diagnostic materials especially for regions limited in resources.